Gender and consumption - Scott, Linda (Henry Stewart Talks, 2013)
Marking sex, Enculturation, Division of labor, Women control consumption, Sophia mind study in Brazil, Women within the global economy, Consumption categories by sex, Parks associates survey, Female influence on household purchases, Women and messaging & social media, Future trends, Implications for management
Reviewed at 2019/02/28